Henry Carrington Bolton papers - Bolton, Henry Carrington, 1843-1903.
Writings, notes, extracts, etc. on uranium compounds, symbols in alchemy, practical chemistry, and other topics.
Collection material in English.
Keywords: Chemistry; Alchemy